USE OF MOTIVATION APPROACHES IN MARKETING ACTIVITIES OF SEWING AND KNITTING ENTERPRISES (Marketing Journal, 2025)
The article explores the essence of motivational approaches. It analyzes the motivational methods used in the marketing activities of sewing and knitwear enterprises. The study also provides recommendations for the application of motivational approaches in the marketing practices of textile and knitwear companies.
Keywords: Content motivation theories; process motivation theories; behavioral motivation theories; cognitive motivation theory; psychological motivation theories; modern theories of motivation